Peningkatan Kemampuan Mengontrol Halusinasi Melalui Terapi Generalis Halusinasi Di RSJD Dr. Arif Zainudin Surakarta - Avica Miftakhul Jannah; Norman Wijaya Gati (Jurnal Ventilator, 2023)
Background: Hallucinations are false perceptual distortions that occur in maladaptive neurobiological responses, sufferers actually experience sensory distortions as real things and respond accordingly. Hallucination sufferers will find it difficult to distinguish between stimuli that arise from internal sources such as thoughts, feelings, somatic sensations and external impulses and stimuli. According to the World Health Organization 2019 mental disorders around the world, according to data, there are 264 million people experiencing depression, 45 million people suffering from bipolar disorder, 50 million people experiencing dementia, and 20 million people experiencing schizophrenia. In this study, how to see an increase in the ability to control hallucinations by using the AHRS scale used to measure the score of auditory hallucinations Objective: Determine the results of the application of generalist hallucination therapy with increased ability to control hallucinations with hallucinatory sensory perception disorders Method: The application of generalist therapy was carried out using a case study descriptive method to 2 respondents for 2 consecutive days. The instrument used is the Auditory Hallucinations Rating Scale (AHRS). Results: based on the results of the application that has been carried out, there is a decrease in the symptoms of auditory hallucinations in patients, with a comparison of the final results between the two respondents for the level of auditory hallucinations, namely 29:34. Conclusion: Generalist therapy can be used as an intervention to improve the ability to control hallucinations in patients with auditory hallucination psychiatric disorders.